2023
DOI: 10.3390/educsci13080816
|View full text |Cite
|
Sign up to set email alerts
|

Storylines in Voices of Frustration: Implications for Mathematics Teacher Education in Changing Times

Abstract: We have interviewed becoming mathematics teachers, in the last semester of their education, asking how they experience their time as teacher students with the focus on inclusive teaching. In their forthcoming daily work, they will be responsible for arranging for inclusive teaching that addresses all the learners’ needs in mathematics. We believe the voices of future teachers are important to include in conversations about how programs prepare future mathematics teachers for the work of teaching in today’s sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…We agree with other colleagues in this Special Issue that critical mathematics education is an important opening for mathematics teaching and teacher education, for reasons already mentioned in the introductory section of this paper, and that its role is crucial for preparing students for a future as democratic citizens [37][38][39][40]. For this to happen in the context of teaching practice, teacher educators and student teachers must envisage themselves as future critical mathematics educators who are able to bring an active discussion of the formatting power of mathematics in society into the school classroom.…”
Section: Discussionsupporting
confidence: 83%
“…We agree with other colleagues in this Special Issue that critical mathematics education is an important opening for mathematics teaching and teacher education, for reasons already mentioned in the introductory section of this paper, and that its role is crucial for preparing students for a future as democratic citizens [37][38][39][40]. For this to happen in the context of teaching practice, teacher educators and student teachers must envisage themselves as future critical mathematics educators who are able to bring an active discussion of the formatting power of mathematics in society into the school classroom.…”
Section: Discussionsupporting
confidence: 83%
“…Although this view is recognized in the mathematics education field, extant research has found that other fields have differing views. For example, mathematics as language-and culture-neutral is one perspective visible in news media, and beginning teachers are frustrated because they have experienced method rigidity in mathematics classrooms [35,36]. Our findings demonstrated that some students were almost invisible during the observed communications (see Tables 1 and 2).…”
Section: The Importance Of Adapted Teaching For Gifted Learnersmentioning
confidence: 73%